2018
DOI: 10.1021/acs.jpca.8b09610
|View full text |Cite
|
Sign up to set email alerts
|

Shedding Light on the Dark Corners of Metal–Organic Framework Thin Films: Growth and Structural Stability of ZIF-8 Layers Probed by Optical Waveguide Spectroscopy

Abstract: Metal–organic framework (MOF) thin films are promising materials for multiple technological applications, such as chemical sensing. However, one potential limitation for their widespread use in different settings is their stability in aqueous environments. In the case of ZIF-8 (zeolitic imidazolate framework) thin films, their stability in aqueous media is currently a matter of debate. Here, we show that optical waveguide spectroscopy (OWS), in combination with surface plasmon resonance (SPR) spectroscopy, off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 61 publications
0
36
0
Order By: Relevance
“…Luminescent materials have a variety of practical applications in optical devices, e.g., optical waveguide used as the transmission medium in local and long haul optical communication systems or the components in integrated optical circuits, , light sources (fluorescent lamps and LEDs), disinfection, medical imaging, horticulture, temperature sensors, and chemical sensors, and so on; thus, lots of research attention has always been paid to exploring a new family of luminescent materials. …”
Section: Introductionmentioning
confidence: 99%
“…Luminescent materials have a variety of practical applications in optical devices, e.g., optical waveguide used as the transmission medium in local and long haul optical communication systems or the components in integrated optical circuits, , light sources (fluorescent lamps and LEDs), disinfection, medical imaging, horticulture, temperature sensors, and chemical sensors, and so on; thus, lots of research attention has always been paid to exploring a new family of luminescent materials. …”
Section: Introductionmentioning
confidence: 99%
“…20,52 ZIF-8 can be described as an infinite network of Zn 2+ ions tetrahedrally coordinated with 2-methylimidazolate N-bidentate organic linkers, featuring high BET surface area (≈ 1500-1800 m 2 g -1 ), and good resistance towards hydrolysis in moderate pH aqueous environments and ionic strengths. 53,54 We show for the first time that a LbL architecture is achievable using these presynthesized nanostructures; and moreover, that these films feature electrochemical activity and can act as enhancers of the neutral pH electrochemical ORR due to a synergetic effect between high surfacearea porous material and electroactive conductive polymer, offering thus a cost-effective alternative to precious metal catalysts usually employed in energy conversion devices.…”
Section: Introductionmentioning
confidence: 90%
“…For example, we have shown that the immobilization of catalase using ZIF-8 generates an inactive biocomposite, attributed to protein unfolding upon interaction with the hydrophobic framework . There are examples within the literature, however, of catalase@ZIF-8 remaining active when stored and tested in phosphate-buffered saline (PBS). Recently, it was demonstrated that pure ZIF-8 particles can rapidly decompose in the presence of phosphate anions. Accordingly, we were motivated to develop our understanding of how the synthesis, and test conditions, affect the particle size, chemistry, and properties of enzyme@ZIF-8 biocomposites.…”
Section: Introductionmentioning
confidence: 99%